2004
DOI: 10.1002/ijc.20397
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical investigation of SV40 large T antigen in Hodgkin and non‐Hodgkin's lymphoma

Abstract: DNA sequences from simian virus 40 (SV40) have been detected in various human tumors, including non-Hodgkin's lymphomas (NHLs), by highly sensitive PCR techniques. However, there is a strong debate as to whether SV40 is present in lymphoma cells. Using immunohistochemistry and tissue microarrays, we investigated a series of French and Canadian cases of Hodgkin's lymphomas (HLs) and NHLs and tried to detect the SV40 large T antigen using routine paraffin sections with standard and highly sensitive catalyzed sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…A recent meta-analysis of data from 589 primary brain cancer samples and 414 control samples conclusively established that SV40 is significantly associated with those malignancies. 17 Although very complete, that paper lacked important data, recently published 6 18 or in press, 19 showing negative results in particular in lymphomas. In a recent study, 19 using the same immunohistochemical approach, we were unable to detect positivity in 482 cases of lymphoma from France and Canada.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis of data from 589 primary brain cancer samples and 414 control samples conclusively established that SV40 is significantly associated with those malignancies. 17 Although very complete, that paper lacked important data, recently published 6 18 or in press, 19 showing negative results in particular in lymphomas. In a recent study, 19 using the same immunohistochemical approach, we were unable to detect positivity in 482 cases of lymphoma from France and Canada.…”
Section: Resultsmentioning
confidence: 99%
“…17 Although very complete, that paper lacked important data, recently published 6 18 or in press, 19 showing negative results in particular in lymphomas. In a recent study, 19 using the same immunohistochemical approach, we were unable to detect positivity in 482 cases of lymphoma from France and Canada. Our results are clearly at variance with those recently presented at the meeting of the American Association for Cancer Research by Samaniego and colleagues 20 and Vilchez et al 21 22 Samaniego et al, 20 found an unusual pattern of staining with the anti-Tag (Pab419) antibody.…”
Section: Resultsmentioning
confidence: 99%
“…Tissue probes of both ureters were stained for SV40 large T antigen (clone pAb416, Oncogene Science, Boston, Mass, USA; dilution 1 : 100, antigen retrieval and amplification with catalyzed system amplification, Dako, Carpinteria, CA). The reactions were detected by means of the streptavidin-biotin method and were revealed using diaminobenzidine as a chromogen [15, 16]. In all tissue probes immunohistochemistry for large T antigen was negative (Figure 3(b)).…”
Section: Case Reportmentioning
confidence: 99%
“…The authors concluded that the inconsistent, low-level detection of SV40 DNA in mesothelioma specimens in their laboratory, and perhaps other laboratories, was likely to be the result of contamination of PCR reagents or tissue specimens by cloning vectors [15]. Likewise, recent studies that have used immunohistochemistry have failed to identify the presence of T-antigen in tumor cells [15,52]. Therefore, it remains uncertain whether SV40 DNA is actually present in human tumors.…”
Section: Expert Opinionmentioning
confidence: 99%